Changes in life satisfaction over six years in the general population: A longitudinal study with the Satisfaction With Life Scale (SWLS) - Andreas Hinz; Anja Mehnert-Theuerkauf; Heide Glaesmer; Matthias L. Schroeter; Ana N. Tibubos; Katja Petrowski; Michael Friedrich (PLoS ONE, 2025)
Background Satisfaction with life is a key concept for most individuals. The Satisfaction With Life Scale (SWLS) for measuring general life satisfaction has been widely analyzed in terms of cross-sectional associations. However, the knowledge about long-term changes in life satisfaction and the associations between such changes and changes in other variables of physical and mental health is limited. Methods A community-based representative sample of the general population has been examined twice with a time interval of six years (n = 4,999), using the SWLS and several other scales. Results Over the six years, the mean SWLS score of the total sample remained nearly unchanged (M = 27.0, SD = 5.2, both at t1 and at t2). The test-retest correlation was rtt = 0.66 for the total sample, and there were only marginal differences in temporal stability between male and female respondents. Changes in the SWLS over the six years were correlated with changes in optimism (r = 0.23), mental health (r = 0.26), social functioning (r = 0.22), perceived social support (r = 0.21), anxiety (r = -0.30), and physical complaints (r = -0.18). These change score correlations were lower than the corresponding coefficients under the cross-sectional perspective. Measurement invariance across sex, age, and time was established. Conclusion The SWLS proved to be an appropriate tool for assessing changes in life satisfaction, and correlations between change scores of life satisfaction and health-related variables complement the knowledge about these associations from a cross-sectional perspective.